Socioeconomic status and self-reported asthma in Indigenous and non-Indigenous Australian adults aged 18-64 years: analysis of national survey data - Cunningham Joan (BMC, 2010)
Abstract Background Asthma is more common among Indigenous than non-Indigenous Australian adults, but little is known about socioeconomic patterning of asthma within the Indigenous population, or whether it is similar to the non-Indigenous population. Methods I analysed weighted data on self-reported current diagnosed asthma and a range of socio-economic and demographic measures for 5,417 Indigenous and 15,432 non-Indigenous adults aged 18-64 years from two nationally representative surveys conducted in parallel by the Australian Bureau of Statistics in 2004-05. Results Current asthma prevalence was higher for Indigenous than non-Indigenous people in every age group. After adjusting for age and sex, main language and place of residence were significantly associated with asthma prevalence in both populations. Traditional SES variables such as education, income and employment status were significantly associated with asthma in the non-Indigenous but not the Indigenous population. For example, age-and sex-adjusted relative odds of asthma among those who did not complete Year 10 (versus those who did) was 1.2 (95% confidence interval (CI) 1.0-1.5) in the non-Indigenous population versus 1.0 (95% CI 0.8-1.3) in the Indigenous population. Conclusions The socioeconomic patterning of asthma among Indigenous Australians is much less pronounced than for other chronic diseases such as diabetes and kidney disease, and contrasts with asthma patterns in the non-Indigenous population. This may be due in part to the episodic nature of asthma, and the well-known challenges in diagnosing it, especially among people with limited health literacy and/or limited access to health care, both of which are more likely in the Indigenous population. It may also reflect the importance of exposures occurring across the socioeconomic spectrum among Indigenous Australians, such as racism, and discrimination, marginalization and dispossession, chronic stress and exposure to violence.